Switch programming of reflectivity control devices for the coupled dynamics of a solar sail. Issue 5 (1st March 2016) - Hu, Tianjian; Gong, Shengping; Mu, Junshan; Li, Junfeng; Wang, Tianshu; Qian, Weiping
Abstract: As demonstrated in the Interplanetary Kite-craft Accelerated by Radiation Of the Sun (IKAROS), reflectivity control devices (RCDs) are switched on or off independently with each other, which has nevertheless been ignored by many previous researches. This paper emphasizes the discrete property of RCDs, and aims to obtain an appropriate switch law of RCDs for a rigid spinning solar sail. First, the coupled attitude–orbit dynamics is derived from the basic solar force and torque model into an underdetermined linear system with a binary set constraint. Subsequently, the coupled dynamics is reformulated into a constrained quadratic programming and a basic gradient projection method is designed to search for the optimal solution. Finally, a circular sail flying in the Venus rendezvous mission demonstrates the model and method numerically, which illustrates approximately 10 3  km terminal position error and 0.5 m/s terminal velocity error as 80 independent RCDs are switched on or off appropriately.